2017
DOI: 10.3747/co.24.3754
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improved Goals-Of-Care Documentation in Advanced Cancer: Report on the Development of a Quality Improvement Initiative

Abstract: Background Documentation of advance care planning for patients with terminal cancer is known to be poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…In this cohort of patients, pre‐study GOC completion rate was high compared to other studies, 18,24 albeit in keeping with previous inpatient studies from our centre 20 . The combination of a communication skills refresher course and verbal prompting of the patients' current GOC improved documentation of GOC during routine clinic reviews of patients with advanced lung cancer.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this cohort of patients, pre‐study GOC completion rate was high compared to other studies, 18,24 albeit in keeping with previous inpatient studies from our centre 20 . The combination of a communication skills refresher course and verbal prompting of the patients' current GOC improved documentation of GOC during routine clinic reviews of patients with advanced lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…Recognising the barriers to advance care planning, multiple studies have reviewed the impact of various interventions to improve this outcome for patients with life‐threatening illnesses 17–19 . In one study, use of a communication‐priming tool was shown to improve Goals of Care (GOC) discussions from 31% to 74% and documentation of treatment limitations from 17% to 61%, without any impact on patients' depression or anxiety 17 …”
Section: Introductionmentioning
confidence: 99%
“…A recent audit of patients with metastatic lung, pancreatic, colon, and breast cancer receiving palliative chemotherapy at the Cancer Centre of Southeastern Ontario (CCSEO) between 2010 and 2015 revealed that only 6% of patients had a documented GOC discussion and only 47% of patients had been referred to PC. 10…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Prior studies have shown that palliative care can facilitate the receipt of goal-concordant care. [20][21][22] At the end of life, patients who have goals-of-care discussions are more likely to receive comfort-focused care and less likely to experience an in-hospital death. 23 These outcomes are associated with improved satisfaction with care among bereaved caregivers.…”
Section: Discussionmentioning
confidence: 99%